Perpetrators and accessories in international criminal law : individual modes of responsibility for collective crimes - Jain, Neha, 1982- (Hart Publishing, 2014)
The author proposes doctrines of perpetration and secondary responsibility that reflect the role and function of high level participants in mass atrocity while situating them within the political and social climate which renders these crimes possible.